2012
DOI: 10.5751/ace-00551-070205
|View full text |Cite
|
Sign up to set email alerts
|

Use of Occupancy Models to Evaluate Expert Knowledge-based Species-Habitat Relationships

Abstract: . 2012. Use of occupancy models to evaluate expert knowledge-based species-habitat relationships. Avian Conservation and Ecology 7(2): 5. http://dx.doi. org/10.5751/ACE-00551-070205 ABSTRACT. Expert knowledge-based species-habitat relationships are used extensively to guide conservation planning, particularly when data are scarce. Purported relationships describe the initial state of knowledge, but are rarely tested. We assessed support in the data for suitability rankings of vegetation types based on expert k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Simulation studies have shown that even a weaker correlation ( θ = 0.10, θ ’ = 0.50) could significantly bias estimates of ψ (Hines et al ., ), indicating the importance of considering correlation along linear transects of point counts. Detections in the BBS are also correlated for the Brown‐headed Nuthatch ( Sitta pusilla ) and Eastern Wood‐Pewee ( Contopus virens ), but not for the Red‐headed Woodpecker ( Melanerpes erythrocephalus ), indicating that correlated detection occupancy models may often, but not always, be preferred over standard occupancy models (Iglecia et al ., ; Hines et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Simulation studies have shown that even a weaker correlation ( θ = 0.10, θ ’ = 0.50) could significantly bias estimates of ψ (Hines et al ., ), indicating the importance of considering correlation along linear transects of point counts. Detections in the BBS are also correlated for the Brown‐headed Nuthatch ( Sitta pusilla ) and Eastern Wood‐Pewee ( Contopus virens ), but not for the Red‐headed Woodpecker ( Melanerpes erythrocephalus ), indicating that correlated detection occupancy models may often, but not always, be preferred over standard occupancy models (Iglecia et al ., ; Hines et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…To address this lack of conformity, we used expert knowledge to allow for synthesis among bycatch records. Expert knowledge has been shown to be a necessary approach to account for data gaps and synthesize existing knowledge and disparate data (26)(27)(28)(29). Our expert panel consisted of 17 independent experts (5,6, and 6 experts with expertise in seabirds, marine mammals, and sea turtles, respectively) with at least 5 y of experience in fisheries bycatch evaluating the intensity of each bycatch record from high (five) to low (one) within each gear category type.…”
Section: Significancementioning
confidence: 99%
“…during the breeding season drive changes in bird distributions because inappropriate habitat will not provide sufficient food and shelter for breeding birds (Friggens & Finch, 2015;Iglecia, Collazo, & McKerrow, 2012). For the Eastern Wood Pewee, we defined appropriate habitats as deciduous forest, evergreen forest, and mixed forest (Hamel, 1992).…”
Section: Changes In the Amount Of Appropriate Habitat Locally Availablementioning
confidence: 99%